Effect of Biostimulants on the Yield and Quality of Selected Herbs - Joanna Majkowska-Gadomska; Krzysztof Jadwisieńczak; Anna Francke; Zdzisław Kaliniewicz (Applied Sciences, 2022)
The aim of this study was to determine the effect of amino acid biopreparations on the yield of summer savory, marjoram, and lemon balm, and the concentrations of selected biochemical and mineral compounds in their herbage. The first experimental factor was plant species: summer savory (Satureja hortensis L.) var. Saturn, marjoram (Origanum majorana L.) var. Miraż, and lemon balm (Melissa officinalis L.). The second experimental factor was the effect exerted by two biopreparations, Calleaf Aminovital and Maximus Amino Protect, on herbage yield and quality. In the control treatment, plants were sprayed with water. The analyzed herb species differed considerably in yield and the concentrations of selected biochemical compounds and minerals. Lemon balm was characterized by the highest yield (1.73 kg m−2). Marjoram var. Miraż was characterized by the highest concentrations of reducing sugars (0.89 g 100 g−1 FM) and L-ascorbic acid (39.7 mg 100 g−1 FM). Summer savory was most abundant in total N, K, and Ca. The tested biostimulants contributed to a decrease in nitrate concentrations in the studied plants. The interaction between the experimental factors significantly affected the content of nitrates and mineral compounds and total N, P, K, and Ca in the herbage of the analyzed plant species.